Equivalent Mechanical Model of a Microchannel Plate - Zhang Shengdan; Bai Yonglin; Cao Weiwei; Qin Junjun; Gao Jiarui; Chang Le; Liu Beihong; Hu Zexun; Chu Zhujun; Cong Xiaoqing; Dong Yongwei; Wang Zhigang (Measurement Science Review, 2024)
The microchannel plate (MCP) is an electron multiplier with millions of micro through-holes that must withstand strong vibrations and enormous shocks in spaceborne detectors. To ensure the reliability and robustness of the MCP in space applications, we proposed an equivalent mechanical model of the MCP to investigate its mechanical properties, since the direct creation of the finite element model using the finite element method (FEM) is not feasible. Then, we developed a test system to verify the effectiveness of the equivalent mechanical model. The results show that the error of harmonic response analysis and the test result is less than 10 %, which is acceptable. Finally, we conducted parametric studies of the MCPs and obtained the equivalent mechanical model of the MCPs with different geometric parameters. This study will help researchers to optimize the MCP for aerospace-grade detectors.